Parents' perception on children safe distance: A case study of Kuala Lumpur and Selangor - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah; Abdullah, Muhammad Faris; Shuid, Syafiee; Ponrahono, Zakiah (American Scientific Publishers, 2017)
Rapid development in Malaysia has lead the family institution to experience challenges in ensuring safety of the family members. The safety of children is a serious matter and currently parents tend to be more vigilant on the issues of safety among children. Overall, the study focus on the safe distance allowed by parents or adult families member of their children to travel from their homes to the public places such as schools, shopping mall, public facilities, bus stations and parks. This study adopted quantitative analysis of face to face questionnaire survey distributed to 4,500 respondents in the Klang Valley. The sampling techniques for the data collection were stratified and simple random sampling method. From this study, it was found that the main factors that influenced parents and guardians to allow their children to travel alone or by group are the children age. Based on the analysis, majority of parents and guardians do not allow their children to go to public places especially at night and alone.